Investigating the impact of 'HOHOHO Mobile application’ in improving the language development of form 6 Students - Saiman , Savina (Journal of Islamic, Social, Economics and Development, 2024)
Post-Secondary English Language Curriculum Framework PSELCF, which is aligned with the CEFR, focuses on students' ability to interact with a degree of language structure and language acquisition. However, form 6 students are facing challenges in pronunciation. Students do not acquire and understand spoken language. Additionally, the research of materials for language development has still not been implemented in Malaysia particularly for form 6 students and the teaching and learning process is still tied to conventional methods. Therefore, this research aims to integrate e-learning through ‘HoHoHo Mobile Application to improve the language development of pre university student. The focus of the research is creating e-learning based on TBLT through mobile applications with the aim of students in rural areas. Secondly, obtaining confirmation from experts on e-learning based on TBLT through mobile applications to improve the language development of students in rural areas. Researcher has used quantitative method in this research. As a 1st step researcher has design and develops the mobile apps using the model established by Kemmis and Mactaggart (1998), for the pre university student. After the Apps been used a survey been gaven to the students to evaluate the effectiveness of mobile apps in enhancing students' engagement and participation in classroom activities and to to assess the impact of mobile apps on students' academic performance and comprehension of the subject matter of students' knowledge of linguistic development. This phase will use descriptive statistics for data analysis. Hopefully, this research is beneficial for educators to integrate the use of e-learning through mobile applications into the teaching and learning of English to increase students' motivation in linguistic development.